Investigation of heat generation/absorption on natural convection flow in a vertical annular micro-channel: An exact solution. Issue 1 (19th December 2017) - Jha, Basant Kumar; Aina, Babatunde
Abstract : Purpose: The purpose of this paper is to further extend the work of Weng and Chen (2009) by considering heat generation/absorption nature of fluid. Design/methodology/approach: Exact solution of momentum equation is derived separately in terms of Bessel's function of first and second kind for heat-generating fluid and modified Bessel's function of first and second kind for heat absorbing fluid. Findings: During the course of numerical computations, it is found that skin friction and rate of heat transfer at outer surface of inner cylinder and inner surface of outer cylinder increases with the increase in heat generation parameter while the reverse trend is found in the case of heat absorption parameter. Originality/value: In view of the amount of works done on natural convection with internal heat generation/absorption, it becomes interesting to investigate the effect of this important activity on natural convection flow in a vertical annular micro-channel. The purpose of this paper is to further extend the work of Weng and Chen (2009) by considering heat generation/absorption nature of fluid.